2016
DOI: 10.1088/0957-4484/27/33/332002
|View full text |Cite
|
Sign up to set email alerts
|

Metallic and semiconducting carbon nanotubes separation using an aqueous two-phase separation technique: a review

Abstract: It is known that carbon nanotubes show desirable physical and chemical properties with a wide array of potential applications. Nonetheless, their potential has been hampered by the difficulties in acquiring high purity, chiral-specific tubes. Considerable advancement has been made in terms of the purification of carbon nanotubes, for instance chemical oxidation, physical separation, and myriad combinations of physical and chemical methods. The aqueous two-phase separation technique has recently been demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 106 publications
0
11
0
Order By: Relevance
“…The easiest application of ATPE is for the separation of highly enriched semiconducting SWCNT populations from the parent dispersion. 16,30,31 In my lab this is performed by competing SC with SDS for the SWCNT surface in the ATPE system, most effectively while in the presence of an oxidizing compound such as sodium hypochlorite (NaClO). In the important report of Gui et al, 35 the authors showed that addition of a small quantity of such an oxidizing agent both vastly improved robustness of the semiconducting from metallic separation delity, by effectively setting the redox potential in the ATPE system rather than relying on the ambient level, and could also enable band gap selection, critically between true metallic armchair, (n,m ¼ n), SWCNTs and the k B T level bandgap semi-metallic SWCNTs.…”
Section: Semiconducting From Metallic Swcnt Separationmentioning
confidence: 99%
“…The easiest application of ATPE is for the separation of highly enriched semiconducting SWCNT populations from the parent dispersion. 16,30,31 In my lab this is performed by competing SC with SDS for the SWCNT surface in the ATPE system, most effectively while in the presence of an oxidizing compound such as sodium hypochlorite (NaClO). In the important report of Gui et al, 35 the authors showed that addition of a small quantity of such an oxidizing agent both vastly improved robustness of the semiconducting from metallic separation delity, by effectively setting the redox potential in the ATPE system rather than relying on the ambient level, and could also enable band gap selection, critically between true metallic armchair, (n,m ¼ n), SWCNTs and the k B T level bandgap semi-metallic SWCNTs.…”
Section: Semiconducting From Metallic Swcnt Separationmentioning
confidence: 99%
“…At this early stage, although our semiconducting TPS nanowires exhibit relative low mobility when compared to up-to-date record best carbon nanotubes [34][35][36][37] and silicon nanowires, 38,39 our fabrication method avoids the complexity caused by selection, separation, and protection problems remaining in current 1D system studies. 40 Besides, our STEM and transport results simultaneously indicate the outstanding stability of TPS nanostructures even down to the nanometer scale, which is crucial for next generation modern electronics.…”
mentioning
confidence: 74%
“…CNTs purification is extremely difficult due to the complexity of its impurity components, including metal particles, amorphous carbon, graphitized carbon and fullerene. 15 Currently, CNTs purification methods mainly includes the physical separation (centrifugation, filtration, etc. ), chemical oxidation, or a combination of these two methods.…”
Section: Introductionmentioning
confidence: 99%